Investigation on correlation between bio-waste material morphology and its dielectric properties - Rudraa Devi, Giamasrow (2022)
In Malaysia, 1.2 million tonnes of bio-waste agricultural base waste are disposed of into landfills annually, which is 39% of the total waste produced in our country. This is one of the biggest causes of pollution such as air pollution, water pollution, and global warming in our country. Fabricating of the bio-waste agricultural base dielectric substrate has the protentional to contribute to the reduction of waste in our country and is potentially useful as an alternative material as a dielectric substrate which can be used in any electrical appliances, Printed Circuit Board (PCBs), and antennas. This research highlights a newly developed dielectric material by using the bio-waste agricultural base dielectric substrate. Pineapple leaves are used as the raw material in this research because it is one of the abundantly available waste materials of Malaysia and has not been studied yet as it is required. The Dielectric substrate can absorb and store electromagnetic signals. The absorbent of the dielectric substrate is investigated by analyzing the morphology structure of the dielectric substrate using TM3030 Scanning Electron Microscopy (SEM). To investigate the suitability of this raw material as electromagnetic absorbing material, the element composition of the dielectric substrate is analyzed through EDX Analysis. From this research, the morphology structure of the raw cellulose fiber of the pineapple leaves can be seen meanwhile the powdered cellulose fiber can’t be seen. In terms of element composition, the dielectric substrate with the highest dielectric value has a higher percentage of carbon element and a lower percentage of oxygen element. The highest dielectric value that was obtained through this research is 3.3103. The result of this research shows pineapple leave have more potentially useful as substitute materials for dielectric substrates.